Graduate Students Perceptions Toward the Integration of Heutagogy Approach in Material Development Class - Tatipang, Devilito Prasetyo; Fitra, Muh. Al Fachrizah; Nur, Sahril (Journal of English Culture, Language, Literature and Education, 2025)
This study investigates graduate students' perspectives on integrating the heutagogical approach in a Material Development course, emphasizing its effects on engagement, critical thinking, skill acquisition, and real-world applicability. Heutagogy, or self-determined learning, prioritizes learner autonomy, critical reflection, and the flexibility to tailor learning strategies to individual needs. The research employs a descriptive qualitative design, utilizing Likert-scale questionnaires and interviews to collect data from 15 doctoral students, with five selected for in-depth discussions. Findings indicate that most participants consider heutagogy highly effective in promoting self-directed learning and creativity in material development. Notably, 73% strongly believe this approach will benefit their academic and professional futures, demonstrating its relevance to evolving trends in educational material creation. Additionally, 67% feel confident in their ability to innovate and adapt, while 53% recognize its role in developing transferable skills for interdisciplinary projects. Furthermore, 80% affirm that heutagogy is well-suited for doctoral-level education, reinforcing its value in advanced academic settings. Despite these positive outcomes, challenges remain, particularly regarding students' confidence in mentoring others through heutagogical methods. This underscores the need for further investigation into peer-learning and mentorship strategies within this framework. Overall, the study highlights heutagogy’s effectiveness in fostering critical thinking and adaptability in higher education.